Turkology in Сhina: study of ancient Turkic written artifacts and leading scientists - Massimkhanuly, D.; Abidenkyzy А. (Journal of Oriental Studies, 2023)
China is a country that is not only home to rich and valuable data on ancient Turkic history and culture, but also has been doing a lot of work and success in studying ancient Turkic written artifacts. Especially since the last half of the 70s of the XX century, the study of ancient Turkic written artifacts in China has reached a new quality and a completely high level. In particular, it is known that Chinese scientists have made significant progress in the study of ancient Turkic written artifacts characteristic of the Middle Ages from the point of view of time, especially in the Turfan region, in the Millennium House in Dunhuang, from the peculiarities of the writing and language of ancient monuments of Kultegin, Bilge Kagan, Tonikok, found in the Xinjiang region, the Central Asian region, and other foreign countries. In this article, we will consider in detail the research related to the ancient Turkic written artifacts of the Middle Kingdom, new ideas and new opinions in the works, as well as conclusions. At the same time, a scientific analysis of the main works of scientists who worked tirelessly in the field of research of ancient Turkic artifacts, made a worthy find for the science of Turkology in general, whose names are known in the world of Turkology, will be presented.